Regenerative Endodontic Treatment: Report of Two Cases with Different Clinical Management and Outcomes - Mehrfam Khoshkhounejad; Noushin Shokouhinejad; Salma Pirmoazen (Tehran University of Medical Sciences, 2016)
Endodontic intervention in necrotic immature permanent teeth is usually a clinical challenge. With appropriate case selection, regenerative treatment can be effective, providing a desirable outcome. However, there is still no consensus on the optimal disinfection protocol or the method to achieve predictable clinical outcome. This article presents two cases of regenerative treatment in necrotic immature teeth, using mineral trioxide aggregate (MTA) and BiodentineTM as coronal barriers and different irrigants, which led to different clinical outcomes.